The Effect of Full-Mouth Rehabilitation on Dental Status and Oral Health Conditions for Children with Special Health Care Needs in Jeddah City: A One Year Follow-Up - Omar A. El Meligy,; Manal S. Maashi,; Abdullah S. Al Mushayt,; Abeer M. Al Nowaiser, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Full-mouth rehabilitation under general anesthesia is required to provide safe and effective dental treatment for children with special health care needs who are at high risk of oral diseases. The aim of this study was to assess the effect on oral health among a group of Children with Special Health Care Needs Program, in Jeddah, up to 12 months post-operatively as only few studies have been assessed in Saudi Arabia. Forty children with special needs required were assessed in two hospitals. Children were examined for dental caries, oral hygiene habits, malocclusion, oral hygiene status, and dental plaque preoperatively, 3-, 6-, 9-, and 12-months post-operatively. Follow-up response rate was 87.5%. More than one-half of the study population were boys (63%) within the age group of 5-8 years. Full-mouth rehabilitation has improved oral hygiene status and reduced plaque index scores throughout the study period. Parents/caregivers reported significant (p ? 0.005) compliance with oral hygiene instructions and provision to help with tooth brushing (p ? 0.016). The effect of full mouth rehabilitation under general anesthesia, with 3-month recall visits, had a significant clinical effect on oral hygiene habits, oral hygiene status, and dental plaque extending up to 12 months postoperatively.